Effects of the supplementation of with orange (Citrus sinensis L) peel silage on some metabolic parameters in dairy cows - Cruz Carrillo, Anastasia (2020)
The aim of this study was to determine the effect of orange/oat and only oat silages on the metabolic levels of cows in milk during the summer and on the compositional quality of the milk, looking for alternative feeding during summer without major investments. Twenty healthy cows were distributed in two groups at random. The cows of the first group were supplemented with orange/oat silage and in the second with only oatmeal silage for 30 days. The animals maintained their metabolic status, body condition and milk production. Cholesterol was the only parameter found higher in animals supplemented with orange/oat silage as compared to the animals fed with only oatmeal silage. It is concluded that both types of silage for supplementation is equivalent, but the acceptance by the animals of the orange/oat silage was notoriously superior.